Comparison of Six Commercial Plasma References for Factor VIII, Factor IX and von Willebrand Factor - Kasper, Carol K; Aronson, David L; Davignon, George; Foster, Paul; Hillman-Wiseman, Carol; Lusher, Jeanne M; Manco-Johnson, Marilyn; Meade, James B; Montgomery, Robert R; Rickies, Frederick R; White, Gilbert C, II (Thrombosis and Haemostasis, 1995)
Six brands of normal reference plasma produced in the United States, with assigned assay values for factor VIII and IX and, in four instances, ristocetin cofactor and von Willebrand antigen, were assayed in nine coagulation laboratories in academic institutions in the same country. Differences in mean assays of reference plasmas, as a percent of labelled potency, were significant and were greater than differences among laboratories. Standard methods of assigning potency to commercial reference plasmas are recommended.